Analisa Kinerja Ruas Jalan Karet di Kota Palangka Raya - Faizal Candra Prasetyo; Nirwana Puspasari; Rida Respati (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
Development and growth in various aspects of life and progress in development,give an impact on the increasing number of motorized vehicles. This will result in the amount of current traffic increases, while road capability is limited to service. Increased traffic flow happening on a road will affect the capacity and performance of the road itself along the road rubber has quite a lot of traffic activities. Based on such conditions it is deemed necessary to conduct research to find out whether there are capacity problems and road performance on the road that. To get the data the researcher must direct the space to get the traffic data done for three days. After getting traffic volume data, the data is processed so that get results, where the results are in the form of numbers to find out what the capacity and performance of the road is problematic or not according to MKJI 1997 rules. From the results of the research, the results of the DS rubber road were 368.56 / 1247.62 = 0.30, noon 473.93 / 1290.15 = 0.39, afternoon 492.28 / 1332.68 = 040 still in good condition.